2022
DOI: 10.1038/s41598-022-13944-1
|View full text |Cite
|
Sign up to set email alerts
|

Compact resonant systems for perfect and broadband sound absorption in wide waveguides in transmission problems

Abstract: This work deals with wave absorption in reciprocal asymmetric scattering problem by addressing the acoustic problem of compact absorbers for perfect unidirectional absorption, flush mounted to the walls of wide ducts. These absorbers are composed of several side-by-side resonators that are usually of different geometry and thus detuned to yield an asymmetric acoustic response. A simple lumped-element model analysis is performed to link the dependence of the optimal resonators surface impedance, resonance frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…[40,43] Note that, by using two resonators of the same type, the distance between them in the wave direction should be properly chosen to produce the other type of resonance. [40,44] Alternatively, a degenerate resonator [26,40] could be considered, which is realized by introducing a monopolar and a dipolar resonances at the same position along the wave propagation. The use of degenerate resonators generally results in spatially compact designs for perfect absorption, at the price of a more difficult design process since the evanescent coupling is usually significant.…”
Section: Introductionmentioning
confidence: 99%
“…[40,43] Note that, by using two resonators of the same type, the distance between them in the wave direction should be properly chosen to produce the other type of resonance. [40,44] Alternatively, a degenerate resonator [26,40] could be considered, which is realized by introducing a monopolar and a dipolar resonances at the same position along the wave propagation. The use of degenerate resonators generally results in spatially compact designs for perfect absorption, at the price of a more difficult design process since the evanescent coupling is usually significant.…”
Section: Introductionmentioning
confidence: 99%
“…The nearly perfect transmission phenomenon for electromagnetic and acoustic waves has been extensively researched [33][34][35][36][37][38], while analogous studies have seldom been reported in the field of ultrasonic guided wave based damage detection. In this paper, the interaction between the first Lamé mode and a part-through or through-thickness crack of various sizes is analyzed quantitatively.…”
Section: Introductionmentioning
confidence: 99%